Proposed marketing startegy for pt. Dewa beton using testimonial video based content marketing - Redzky Al-Farisi, Syaefic; Furinto, Asnan (The Indonesian Journal of Business Administration, 2018)
Abstract. Currently, our government are very concern on the infrastructure developments across Indonesia. There are various projections that has been worked starts from the development of LRT until building housing in several region, which all do to improve the nation’s economy. The impact is the construction sector become growing and the demand on building materials are increasing. However, the growth does not happen in PT Dewa Beton. The company has facing decreases sales in the past few years because of the competition become tighter. PT. Dewa Beton is a concrete supplier company that provides building material, particularly in producing and supplying ready-mix concrete. The company and its batching plan is located at Tangerang, Banten.The initial idea of the establishment company is to fulfil the need of concreate againts the number of construction projects in Indonesia, especially in Banten province. Dealing with problems faced by PT Dewa Beton, the research perform in-depth analysis using Porter 5 Forces Pestel Analysis; Service Marketing and SWOT as a form of external analysis and internal analysis. Based on the results of the analysis, the industry is still attractive.In conclusion, the researcher then create a new marketing strategy proposal that involves analysis of Step-by-step Content Marketing andtestimonial story-based promotion video in order to increasing brand awareness of PT Dewa Beton.Keywords: construction indsutry; marketing strategy; content marketing; social media; video marketing